Research needs and prioritizations for studies linking dietary sugars and potentially related health outcomes. Issue 1 (December 2016) - Chung, Mei; Wang, Ding; Archer, Edward; Higgins, Janine; Kim, Sery; Laughlin, Maren; Qi, Lu; Raatz, Susan; Siegel, Richard; Slavin, Joanne; Steffen, Dan; Warshaw, Hope; et al.
Abstract Background Relationships among dietary sugars and a variety of chronic diseases have spawned interest in investigating the metabolic effects of dietary sugars. An approach developed by the Agency for Healthcare Research and Quality (AHRQ) for assessing Future Research Needs (FRN) was implemented with modifications that integrated an evidence mapping process. Methods A panel of 14 stakeholders across 7 pre-defined areas of expertise (lay audience, policy makers, health providers, research funders, evidence-based methodologists, product makers, and researchers) was assembled to prioritize research needs. The panel was facilitated by an independent research team. A total of 213 studies were analyzed descriptively for evidence mapping, and the results were used to inform the stakeholder panel discussions on research needs. Results The stakeholder panel identified and prioritized 14 sets of research questions. The top three high-priority FRN questions selected by the stakeholder panel focused on the effects of dietary sugars on body weight or body composition, fat deposition, and satiety and appetite. Research considerations for the top three research questions and crosscutting research design issues are discussed. Conclusion Involving a multidisciplinary stakeholder panel to prioritize the direction of future research in this or other content areas has potential to add diverse perspectives to the determination of research needs, and to the development of public health policy.